Clinical and Imaging Analysis of Cerebral Infarction Caused by Spontaneous Cerebral Artery Dissection Based on Augmented Reality Technology. (11th February 2021) - Wang, Yinghai; Duan, Kedong; Zhang, Aihua; Lv, Yaping; Cao, Dahai
Abstract : In recent years, with the progress of population ageing, the incidence of a stroke caused by spontaneous dissection of the cerebral artery also increases with time. In order to address the health damage caused by a stroke caused by spontaneous dissection of the cerebral artery and to study its effect on human health, this article analyzes the incidence, type, electrocardiogram, and cardiovascular biomarker changes of cerebral infarction through statistical analysis and then discusses cerebral infarction. The pathogenesis and prevention measures of the disease are expected to provide better means for the treatment of cerebral infarction. Based on the case investigation of patients with cerebral infarction caused by spontaneous cerebral artery dissection, a case template was constructed, and a damage assessment matrix was created using a comprehensive quantitative and qualitative analysis method. Experimental results prove that cerebral infarction caused by spontaneous cerebral artery dissection is a great threat to human health, and the fatality rate of patients is extremely high. Enhanced imaging technology is of great help to clinical and image analysis, with a correlation coefficient of 0.87, compared with the other damage rate of cerebral infarction caused by spontaneous cerebral artery dissection which is about 15% higher than that of cerebral infarction caused by different methods. Studies have found that there are great differences in the age of people with cerebral infarction caused by spontaneous cerebral artery dissection, and the patients are generally over 45 years old. This shows that cerebral infarction caused by spontaneous cerebral artery dissection will cause great damage and affect people's health, which requires people's attention.